Pengaruh Brand ambassador, Brand Image, Dan Online Customer review Terhadap Keputusan Pembelian Konsumen Pada Scarlet Whitening Di Surabaya Barat - Amaluddin, Rival; Asiyah, Siti; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2024)
AbstractÂ This study aims to determine the influence of brand ambassadors, Brand Image and online customer reviews on consumer purchasing decisions in Scarlet Whitening in West Surabaya. The type of research used is quantitative. The sampling method uses the non-probability sampling method, which is a sampling technique according to certain criteria, the sample criteria in this study are customers who have shopped for Scarlet Whitening products aged 18 years and over, the number of samples is set with a minimum of 5 to 10 times the number of indicators, so the number of samples taken in this study is (15x5 = 75). The data analysis method used in this study is multiple linear regression analysis, data processing using the SPSS program version 25 for windows.The results showed that in test F or simultaneously the variables brand ambassador, brand image, and online customer review had a significant effect on purchasing decisions. The results of the t test or partially show that the brand ambassador variable has a positive and significant effect on purchasing decisions, Brand Image variables have a positive and significant effect on purchasing decisions and online customer review variables have a positive and significant effect on purchase decisions.Â Keywords: Brand ambassador, Brand Image, Online Customer Review, Purchase Decision.